Comparative Law of Business Competition between Indonesia and Singapore - Rully Syahrul Mucharom (Universitas Muhammadiyah Surakarta, 2024)
The significant phenomenon of economic globalization is related to the increasingly binding interdependence of relations between nations, especially pe. Of course, this must have legal regulations that regulate so that violations do not occur in the trade sector which could potentially give rise to violations in the business competition sector. This policy includes law enforcement, deregulation policies, foreign direct investment, and other policies related to business competition. Competition law is an important legal tool in encouraging healthy competition and protecting consumers. The theory used in analyzing this paper is comparative law and legal certainty. The conclusion obtained from his research is that Indonesia has Business Competition Law Number 5 of 1999 as the basis for regulating business competition. Singapore has a stronger legal framework in promoting fair competition and protecting consumers, namely the Competition Commission of Singapore (CCS). The countryhas an independent competition authority. For this reason, the author compares it with regulations prohibiting acts of unfair business competition.